2021
DOI: 10.1177/0194599821994477
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Trends in Fellowship Training Among Otolaryngology Residents: A National Survey Study

Abstract: Objective To summarize trends in otolaryngology fellowship applications, fellowships selected, and reasons for pursuing a fellowship. Study Design One-page anonymous questionnaire. Setting A survey was completed by examinees at the conclusion of their American Board of Otolaryngology–Head and Neck Surgery oral examination from 2011 to 2019. Methods Data included age, gender, fellowship type, reasons for doing a fellowship, and type of practice that examinees will enter. Spearman correlation and Pearson chi-squ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 31 publications
2
43
0
Order By: Relevance
“…Miller et al found a statistically significant increase in the amount of otolaryngology residents pursuing fellowship training, with a 15.9% increase in residents pursuing a fellowship from 2011 to 2019. 2 This correlation is consistent with an increasing number of fellowship positions being offered across the various subspecialties. 5 The most common fellowships among this cohort of graduates were facial plastics, head and neck surgery, and pediatric otolaryngology.…”
Section: Discussionsupporting
confidence: 57%
“…Miller et al found a statistically significant increase in the amount of otolaryngology residents pursuing fellowship training, with a 15.9% increase in residents pursuing a fellowship from 2011 to 2019. 2 This correlation is consistent with an increasing number of fellowship positions being offered across the various subspecialties. 5 The most common fellowships among this cohort of graduates were facial plastics, head and neck surgery, and pediatric otolaryngology.…”
Section: Discussionsupporting
confidence: 57%
“…Younger ORLs are also choosing to do fellowship more often. 42 Thus, younger ORLs may be performing more time-intensive complex cases early in their career, and there may be a lack of young generalists. Nevertheless, this pattern does not appear to hold in a comparison between female ORL graduates from 1970 to 1979 and 2000 to 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Results of a recent study surveying otolaryngology residents show that 46% of residents in 2011 chose to complete fellowship in any subspecialty, while 62% of residents in 2019 chose to complete fellowship. 14 Across all years, 19% of residents chose to pursue head and neck oncology. At the current rate of growth of AHNS accredited head and neck fellows, the number of practicing surgeons may eclipse cancer incidence in some states, creating a potential supply-demand mismatch.…”
Section: Discussionmentioning
confidence: 99%